Do Hepatic Encephalopathy Patients Really Need a Low Protein in Their Diet - Untung Sudomo; Syafruddin AR Lelosutan; Ruswhandi Ruswhandi; Nurul Akbar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2007)
Hepatic encephalopathy (HE) is an extra hepatic complication of liver cirrhosis. The clinical manifestation of HE is a reflection of a low-grade cerebral edema due to astrocyte swelling as a consequence of hyperammonia. HE mostly is induced by precipitating factors. Correcting these identifiable precipitating factors can alleviate this complication. In the past, liver cirrhosis patients were recommended to lower their protein intake. It was assumed that by limiting protein intake, the ammonia production would lower, which can lead to HE recovery. This approach, on the other hand, had worsened the nutritional status that already present in most patients with HE. There are some ways to overcome these problems without restricting protein intake including balance diet, using Branch Chain Amino Acids (BCAA), and frequent small portion diet.   Keywords: hepatic encephalopathy, astrocytes swelling, ammonia, liver cirrhosis, BCAA